Anti-hyperalgesic Effect of a Benzilidine-cyclohexanone Analogue on a Mouse Model of Chronic Constriction Injury-induced Neuropathic Pain: Participation of the Îº-opioid Receptor and KATP - Akhtar, Muhammad Nadeem; Shaik Ibrahim, Khalivulla; Lee, Ming-Tatt; Nordin, Lajis; Enoch Kumar, Perimal; Ahmad, Akira; Daud Israf, Ali; Mohd Roslan, Sulaiman (Elsevier, 2013)
The present study investigated the analgesic effect of a novel synthetic cyclohexanone derivative, 2,6-bis-4-(hydroxyl-3-methoxybenzilidine)-cyclohexanone or BHMC in a mouse model of chronic constriction injury-induced neuropathic pain. It was demonstrated that intraperitoneal administration of BHMC (0.03, 0.1, 0.3 and 1.0 mg/kg) exhibited dose-dependent inhibition of chronic constriction injury-induced neuropathic pain in mice, when evaluated using RandallâSelitto mechanical analgesiometer. It was also demonstrated that pretreatment of naloxone (non-selective opioid receptor blocker), nor-binaltorphimine (nor-BNI, selective Îº-opioid receptor blocker), but not Î²-funaltrexamine (Î²-FN, selective Î¼-opioid receptor blocker) and naltrindole hydrochloride (NTI, selective Î´-opioid receptor blocker), reversed the anti-nociceptive effect of BHMC. In addition, the analgesic effect of BHMC was also reverted by pretreatment of 1H-[1,2,4]Oxadiazole[4,3-a]quinoxalin-1-one (ODQ, soluble guanosyl cyclase blocker) and glibenclamide (ATP-sensitive potassium channel blocker) but not NÏ-nitro-l-arginine (l-NAME, a nitric oxide synthase blocker). Taken together, the present study demonstrated that the systemic administration of BHMC attenuated chronic constriction, injury-induced neuropathic pain. We also suggested that the possible mechanisms include Îº-opioid receptor activation and nitric oxide-independent cyclic guanosine monophosphate activation of ATP-sensitive potassium channel opening.